Tau kinetics in Alzheimer disease and primary tauopathies: Development of new models and analysis methods/tau. (7th December 2020) - Sato, Chihiro; Horie, Kanta; Barthelemy, Nicolas R.; Patterson, Bruce W.; Gordon, Brian A.; Benzinger, Tammie L.S.; Mallipeddi, Nipun; Sullivan, Melissa; Li, Melody; Lloyd, LaKisha; Elbert, Donald L.; Wright, Brenton A.; et al.
Abstract: Background: Understanding tau kinetics in the human central nervous system is critical for evaluating the effects of tau‐targeted therapies and designing clinical trials against tau in Alzheimer disease (AD) and other primary tauopathies. We hypothesized that tau production or clearance is altered in tauopathies and measured tau kinetics in AD and in a small set of participants with Progressive Supranuclear Palsy (PSP), Corticobasal Syndrome (CBS), or from Frontotemporal Dementia (FTD)‐ MAPT families. Methods: In vivo human tau Stable Isotope Labeling Kinetics (SILK) were performed in 65 participants including 10 young normal controls, 23 age‐matched controls, 16 AD and 16 primary tauopathies (2 PSP, 4 CBS, 10 MAPT mutation family). Briefly, participants received 16hr intravenous infusion of 13 C6 ‐leucine and cerebrospinal fluid (CSF) was collected from five lumbar punctures over 120 days. Labeled tau was measured with mass spectrometry to obtain kinetic curves of tau. Production and clearance rates were calculated and compared across different tauopathies. CSF amyloid beta (Aβ), amyloid and tau Positron Emission Tomography (PET) imaging were measured in a subset of participants, and analyzed for correlation with SILK measures. Results: First, we confirmed the reproducibility of previous results (Sato et al., 2018) and demonstrated that tau production rates increased with amyloid measured by PET or CSF Aβ. Second, CSF tau concentration correlated with CSF Aβ40 and Aβ42 in primary tauopathies but only with Aβ40 in those with abnormal Aβ levels. Third, 2 PSP patients had slower clearance of tau with tau half‐lives approximately 1.5‐2.5 times longer than other cohorts. Tau Fractional Synthesis Rate also negatively correlated with tau concentration in primary tauopathies, and CBS and FTD‐ MAPT had different slopes, suggesting that they may have different kinetics. Conclusions: The results from this study provide mechanistic insights into differences between AD and other primary tauopathies, which may be targeted differently when developing therapies against tau metabolism. In vivo tau kinetics can help evaluate the efficacy of tau‐targeted therapies and provide information for designing clinical trials targeting tau.